Healthcare provider perspectives on barriers and facilitators to integration of cardiovascular disease-related care into HIV care and treatment clinics in urban Tanzania - Ottaru, Theresia A.; Ngakongwa, Fileuka C.; Butt, Zeeshan; Hawkins, Claudia A.; Kaaya, Sylvia F.; Metta, Emmy O.; Chillo, Pilly; Siril, Helen N.; Hirschhorn, Lisa R.; Kwesigabo, Gideon P. (Frontiers in Public Health, 2024)
BackgroundThe increase in the dual burden of HIV and cardiovascular diseases (CVD), calls for the provision of integrated HIV/CVD care. This study aimed to explore barriers and facilitators to the integration of HIV/CVD care within HIV care and treatment clinics (CTCs) in urban, Tanzania.MethodsBetween March and April 2023, we conducted 12 key informant interviews with healthcare providers at six HIV CTCs in urban, Tanzania. Guided by the Consolidated Framework for Implementation Research (CFIR 1.0), we designed the interview guide and conducted a thematic analysis.ResultsOut of the 11 CFIR constructs explored, three were barriers (cost, availability of resources, and access to information and knowledge), six were facilitators (complexity, relative advantage, patient needs, external policies and incentives, relative priority, and knowledge and belief about the intervention), and two (compatibility and self-efficacy) were both barriers and facilitators. Barriers to integration included a lack of equipment, such as BP machines, lack of space, unavailability of an electronic data-capturing tool at the HIV CTCs for monitoring CVD outcomes, and a shortage of trained healthcare workers, particularly in managing CVD comorbidities according to current recommendations. Providers acknowledged the increasing demand for CVD care among ALHIV and regarded integration as not a complex task. Providers reported that both services could be delivered simultaneously without disrupting client workflow and were determined to offer integrated care within HIV CTCs. Providers expressed concerns about medication costs and recommended that medications should be provided for free as part of the integrated care.ConclusionEffective and sustainable HIV/CVD integrated care requires an understating of the existing barriers and facilitators within the HIV CTCs. This study identifies key barriers at HIV CTCs that must be addressed and facilitators to be leveraged before CVD care is integrated into HIV CTCs to ensure that CVD care is delivered effectively within an integrated system.